2006
DOI: 10.1016/j.virol.2005.09.019
|View full text |Cite
|
Sign up to set email alerts
|

Conserved molecular systems of the Baculoviridae

Abstract: Although the Baculoviridae are a large and diverse family of viruses, they are united by a number of shared features that form the basis for their unique life cycle. These include the mechanism of cell entry, genome replication and processing, and late and very late gene transcription. In this review, the molecular systems that are conserved within the Baculoviridae and that are responsible these processes are described.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
54
0
8

Year Published

2008
2008
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(63 citation statements)
references
References 90 publications
1
54
0
8
Order By: Relevance
“…After 1 h of virus adsorption, infected cells were rinsed once with fresh medium and then incubated at 28°C. At different times postinfection, viral yields were determined by a 50% tissue culture infective dose (TCID 50 ) endpoint dilution assay on Sf21 cells and calculated according to the Reed-Muench method (31). For all the infections, time zero (0 hpi) was considered to be the time when the monolayer was replenished with fresh medium after the unadsorbed virus had been aspirated from the wells.…”
Section: Cells and Virusesmentioning
confidence: 99%
See 2 more Smart Citations
“…After 1 h of virus adsorption, infected cells were rinsed once with fresh medium and then incubated at 28°C. At different times postinfection, viral yields were determined by a 50% tissue culture infective dose (TCID 50 ) endpoint dilution assay on Sf21 cells and calculated according to the Reed-Muench method (31). For all the infections, time zero (0 hpi) was considered to be the time when the monolayer was replenished with fresh medium after the unadsorbed virus had been aspirated from the wells.…”
Section: Cells and Virusesmentioning
confidence: 99%
“…AcMNPV replicates its large (134-kb), circular, double-stranded DNA genome (1) in the nucleus of infected cells following a molecular interaction between virus-encoded transacting factors and cis-acting DNA sequences. To date, the functional roles of only some trans-acting factors involved in DNA replication have been elucidated (24,31).The AcMNPV DNA polymerase (DNApol) plays an essential role in AcMNPV DNA replication (27,48). The 3-kb DNApol open reading frame (ORF) encodes a polypeptide of 984 amino acids (aa) with a predicted molecular mass of 114.31 kDa (46).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The genes directly involved in DNA replication (reviewed in Rohrman, 2011) encode for a homologous-region (hr) binding protein and transcriptional activator (ie-1) (Leisy et al, 1995;Rodems & Friesen., 1995), a single-stranded DNA binding protein (lef-3) (Hang et al, 1995), DNA binding helicase (p143) (McDougal & Guarino, 2000), a putative primase (lef-1), a primase-associated protein (lef-2) (Mikhailov & Rohrmann, 2002) and a DNA polymerase (dnapol) (Hang & Guarino, 1999;McDougal & Guarino, 1999). Four of these genes, dnapol, p143, lef-1, and lef-2 are core genes found in all baculoviruses (Okano et al, 2006). Other genes such as ie-2, lef-7, pe38, and p35, stimulate viral DNA replication in transient assays (Chen & Thiem, 1997;Lu & Miller, 1995a;Milks et al, 2003) and were found to be differentially required in cell lines from various lepidopteran origins as well as in vivo (Chen & Thiem, 1997;Lu & Miller 1995b;Milks et al, 2003;Prikhod'ko et al, 1999).…”
Section: Late Phase -Dna Replicationmentioning
confidence: 99%
“…On the contrary, the expression of late and very late genes is dependent on viral DNA replication and the presence of early viral gene products (Blissard and Rohrmann, 1990). The delayed early helicase gene, which was found in all baculovirus genomes sequenced to date, is one of six essential genes in baculovirus DNA replication in transient assays (Kool et al, 1994;Okano et al, 2006). According to the transient expression assays using luciferase as reporter, the helicase promoter can initiate detectable transcription without any viral product in Bm cells, and the transcription level is much higher when the Bm cells were infected with the BmNPV (Xiao et al, 2001).…”
Section: Introductionmentioning
confidence: 99%